The transfection efficiency of calix[4]arene-based lipids: the role of the alkyl chain length. (11th December 2014) - Mochizuki, Shinichi; Nishina, Koichi; Fujii, Shota; Sakurai, Kazuo
Abstract : Calix[4]arene-based lipids with the C6 alkyl chain length exhibited the highest transfection efficiency among all lipoplexes comprising the lipids with different alkyl chain lengths and plasmid DNA. Abstract : The size, surface charge, and microstructure of lipoplexes comprising cationic lipids and nucleic acids are important factors for transfection efficiency. As these properties are largely determined by the cationic lipids used, a number of studies on the relationship between cationic lipids and the transfection efficiency have been reported. Among the many cationic lipids, lipids with multivalent cationic head groups are expected to be potent transfection reagents. Here, we prepared calix[4]arene-based lipids with different alkyl chain lengths from C3 to C15 and evaluated the relationship between the alkyl chain length and the transfection efficiency. C6 lipoplexes exhibited the highest transfection efficiency among all lipoplexes. The gene expression with C9 and C12 lipoplexes was slightly lower than that with C6 lipoplexes. C3 lipoplexes hardly induced gene expression, while C15 lipoplexes exhibited no complexation with plasmid DNA. Although all lipoplexes exhibited nearly identical characteristics, they exhibited different behaviours in terms of the interactions between the lipoplexes and anionic micelles comprising phosphatidylserine, a model of endosomal vehicle. After mixing with phosphatidylserine micelles, C6 lipoplexes released the bound plasmid DNA at pH 5 but not at pH 7, indicating that they can interact with the late endosomal membrane after being incorporated into cells. No plasmid DNA was released from C9 or C12 lipoplexes at either pH values. Thus, the alkyl chain length of cationic lipids is related to their interaction with the endosomal compartment and can provide a basis for the design of novel transfection reagents.